Hormone Depletion-Insensitivity of Prostate Cancer Cells Is Supported by the AR Without Binding to Classical Response Elements - Gonit, Mesfin (Endocrine Society, 2011)
A need for androgen response elements (AREs) for androgen receptor (AR)-dependent growth of hormone depletion-insensitive prostate cancer is generally presumed. In such cells, androgen-independent activation by AR of certain genes has been attributed to selective increases in basal associations of AR with putative enhancers. We examined the importance of AR binding to DNA in prostate cancer cells in which proliferation in the absence of hormone was profoundly (∼90%) dependent on endogenous AR and where the receptor was not up-regulated or mutated but was predominantly nuclear. Here, ARE-mediated promoter activation and the binding of AR to a known ARE in the chromatin remained entirely androgen dependent, and the cells showed an androgen-responsive gene expression profile with an unaltered sensitivity to androgen dose. In the same cells, a different set of genes primarily enriched for cell division functions was activated by AR independently of hormone and significantly overlapped the signature gene overexpression profile of hormone ablation-insensitive clinical tumors. After knockdown of endogenous AR, hormone depletion-insensitive cell proliferation and AR apoprotein-dependent gene expression were rescued by an AR mutant that was unable to bind to ARE but that could transactivate through a well-established AR tethering protein. Hormone depletion-insensitive AR binding sites in the chromatin were functional, binding, and responding to both the wild-type and the mutant AR and lacked enrichment for canonical or noncanonical ARE half-sites. Therefore, a potentially diverse set of ARE-independent mechanisms of AR interactions with target genes must underlie truly hormone depletion-insensitive gene regulation and proliferation in prostate cancer.